Intro to NumPy - Dennison, Justin; Boose, Cherokee; Rysdam, Peter van (Packt Publishing, 2024)
Embark on a foundational journey with NumPy, starting with an overview and setting up the scientific Python environment. This course refreshes Python basics using Jupyter notebooks, preparing you to explore NumPy arrays. Learn array creation, manipulation, and the various supported data types, building a strong foundation for complex operations. Progress through essential concepts like indexing, slicing, and the differences between copies and views of arrays. Discover the power of elementwise and broadcasting operations for efficient numerical computations. Engage in hands-on exercises in graphing and visualization to present your data effectively. Topics such as reduction, shape, and sort operations are covered in detail, equipping you to manipulate large datasets with ease. In the final section, delve into specialized topics like structured arrays and data type management, including casting and size considerations. The course culminates in a practical project on time series analysis, applying all the skills learned to real-world data. This project-based approach ensures you understand both the theoretical aspects and gain practical experience using NumPy for scientific computing and data analysis.
Online resource; title from title details screen (O'Reilly, viewed June 18, 2024)
Keywords: Python (Computer program language); Computer programming; Python (Langage de programmation); Programmation (Informatique); computer programming; Instructional films; Nonfiction films; Internet videos; Films de formation; Films autres que de fiction; Vidéos sur Internet